"Und wann kümmern wir uns um den Fahrer?" - Erstbetreuung als Teil der Versorgung bei drohender psychischer Traumatisierung im Fahrdienst: Bedeutung für die arbeitsmedizinische Versorgungspraxis - Clarner, Annika; Wrenger, Nina; Voss, Amanda Sophie; Uter, Wolfgang; Martin, A.; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
Background and objective: Events causing fatalities and serious damage occur in the railway, transportation and regional public transport (OPNV) sector every year. From the perspective of occupational medicine, it is essential to provide adequate care for drivers who are potentially at risk of psychological trauma. A widespread concept of provision is first-response systems in the form of layman- based acute care after accidents at work involving drivers (VBG [German accident insurance provider]). The objective of this paper was a scientific evaluation of these systems. Methodology: Two retrospective cohort studies were conducted with regard to factors influencing length of absence and illness progression among drivers working for two German transport companies in Bavaria and Hesse. Whilst the first study investigated factors influencing post-traumatic stress following first response care, the second cohort study examined the efficacy associated with different forms of first response (collegial, hierarchical or none). The study covered accidents at work between 2003 and 2013. Results: The pilot study covered 59 first response deployments. It was possible to analyse the progression of 259 cases of illness among drivers within the scope of the main study. Accidents in which the casualties were seriously or fatally injured constituted the strongest predictor for drivers. Differences relating to response systems were found in terms of the length of absences when slight damage occurred. There was clear evidence in the control group of an insignificant trend towards a reduction in periods of absence and a significantly low score for the development of post-traumatic stress. Conclusions: When it comes to the form of acute care provision, peer-based systems with an eye to periods of absence may be classed as worth recommending in the case of events causing less serious damage. On the other hand, it is not possible to infer a switchover to the English guideline (NICE) in the sense of "watchful waiting" without first response for Germany in future. The severity of injury is the biggest factor in post-traumatic stress after traumatic events in driving jobs and necessitates binding regulations for damaging events of this kind and accompanying research in the field of occupational medical care.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Accident; Incapacity for work or PTSD; Traffic; Transport; Trauma